Symposium on Genetics in Gynecology and Obstetrics. - Quiroga de Michelena, María Isabel (2015)
Genetic medicine is a rapidly developing specialty, which in recent years has undergone a real conceptual revolution and a notable increase in the diagnostic capacity at the level of chromosomes, genes and molecules. Advances in genetic influence in almost all medical specialties, but is in gynecology and obstetrics where this relationship is closer and meaningful.